The problem is as follows

If $x^2+x-1=0$, compute all possible values of $\frac{x^2}{x^4-1}$

This was a no-calculator 10 min for 2 problem format contest.

I started by using quadratic formula, but the answers I got were too ugly to be plugged into the equation before time ran out. I tried several algebraic manipulations, but after losing time on the other problem, i found no quick answer to this. I presume there is one step i'm missing to make that leap. Can this be done easily?

  • $\begingroup$ $x^4-1$ factors out to $(x^2+1)(x+1)(x-1)$. $\endgroup$ – Jason Chen May 18 '14 at 5:02



$$=\frac{1-x}{1-3x}\ \ \ \ (1)$$

$$=\frac13\left(1+\frac2{1-3x}\right)\ \ \ \ (2)$$

Now put the two values of $x$, one by one in either $(1)$ or in $(2)$ which ever you like

| cite | improve this answer | |
  • $\begingroup$ Regardless of how practical this may be in the short time-frame I had, I respect its compacting into one equation. $\endgroup$ – Asimov May 18 '14 at 5:11

Use the quadratic formula and solve for the zeros.

Verify that they are $x = \frac{1}{2}(-1-\sqrt{5}),\frac{1}{2}(\sqrt{5}-1)$.

Now just evaluate the later for these values of $x$.

$\textbf{Extra}$: You can also complete the square and you will get: $(x+\frac{1}{2})^2 -\frac{5}{4}=0$, then solve for $x$.

| cite | improve this answer | |
  • $\begingroup$ Taking that to the fourth power was what was giving me difficulty, I had gotten that far, and was wondering if there was a different route. $\endgroup$ – Asimov May 18 '14 at 5:03
  • $\begingroup$ Yes, complete the square and you will get: $(x+\frac{1}{2})^2 -\frac{5}{4}=0$, then solve for $x$. $\endgroup$ – Mr.Fry May 18 '14 at 5:04
  • $\begingroup$ I meant after i got those values, if there was an easier way to find $\frac{x^2}{x^4-1}$ without having to find x. An algebraic way around the ugly part. $\endgroup$ – Asimov May 18 '14 at 5:06
  • $\begingroup$ Oh yes: As @Jason Chen says, $(x^4-1)=(x^2+1)(x+1)(x-1)$. I hope this answered your question :). $\endgroup$ – Mr.Fry May 18 '14 at 5:08
  • $\begingroup$ Ok, I know how to do that, I was just wondering if there was a concise shortcut that removed that part entirely. I guess there may not be in this case. $\endgroup$ – Asimov May 18 '14 at 5:08

Let $a, b$ be the roots of $x^2+x-1=0$. Then $a+b = -1, ab = -1$. For simplicity, consider now the reciprocals of the values we wish to find, i.e. $\dfrac{a^4-1}{a^2} = k_1$ and $\dfrac{b^4-1}{b^2} = k_2$, then

$$k_1 + k_2 = a^2+b^2-\left(\frac1{a^2}+\frac1{b^2} \right), \quad k_1 k_2 = \frac{(a^4-1)(b^4-1)}{(ab)^2}$$

Now $a^2+b^2 = (a+b)^2-2ab = 3$, so $k_1 + k_2 = 3-3=0$.
Also $(a^4-1)(b^4-1) = 1+(ab)^4-(a^4+b^4) = 1+1-(3^2-2) = -5$, so $k_1 k_2 = -5$.

So $k_1, k_2$ are roots of $y^2-5=0 \implies \{k_1, k_2\} = \{\sqrt5, -\sqrt5\}$. Take reciprocals now.

| cite | improve this answer | |

If $x^2+x-1=0$, then $x^2=1 – x$

Squaring both sides, we get $x^4=1 – 2x + x^2$

∴ $x^4 – 1 = x^2 – 2x$

$= (1 – x) – 2x$

$= 1 – 3x$

Thus, the expression $=$ ${1 – x} \over {1 – 3x}$

By long division, it is equivalent to ${1} \over {3}$+ ${2}\over {3(1 – 3x)}$

Edit (1) - Please ignore the following:-

As pointed out, $x^4 – 1$ can also be factorized as $(x^2+1)(x+1)(x-1)$.

Thus, the expression can take any value of x except 1, -1, or 1/3 (if real values of x are assumed).

Edit (2) - Please add the following:-

As pointed out, $x = \frac{1}{2}(-1 \pm \sqrt{5})$

Just put $x = \frac{1}{2}(-1 + \sqrt{5})$ in the simplified expression and do a little rationalization first. For the $x = \frac{1}{2}(-1 - \sqrt{5})$, the result is very similar.

Using the simplified expression, 10 minutes should be sufficient.

| cite | improve this answer | |
  • $\begingroup$ I didn't downvote, but $x$ can only take two values, so this expression can only take two values. $\endgroup$ – Empy2 May 18 '14 at 5:37
  • $\begingroup$ Solution has been edited. Thanks for pointing that out. $\endgroup$ – Mick May 18 '14 at 8:53
  • $\begingroup$ You cannot square both sides before you have proved that $1-x$ takes non-negative values only. $\endgroup$ – user26486 May 18 '14 at 15:29
  • $\begingroup$ I think squaring both sides is allowable (but after that its reverse process should not be conducted because extraneous root(s) will be generated). $\endgroup$ – Mick May 19 '14 at 4:17
  • $\begingroup$ I'm not sure what you mean. Consider the equation $f(a)=f(b)$. Then according to you $f^2(a)=f^2(b)\implies f(a)=f(b)$, but consider, e.g., $3=-3$ and you'll see where you're wrong. And please add @mathh to your comment addressing me since I won't be able to see it otherwise; you are lucky I've accidentally stumbled across this question again. $\endgroup$ – user26486 May 24 '14 at 2:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.